Praksis Pengharapan di Masa Sulit - FX. EKO ARMADA RIYANTO (Sekolah Tinggi Widya Sasana, 2021)
In this article, the author sheds light on the theme of “hope” in three sections, namely: the praxis of hope, hope in Emmanuel Levinas’ philosophy, and hope in the theology of Johann Baptist Metz. Despite its crucial role in human existence, hope is rarely discussed in philosophy. Difficult life events, such as this covid-19 pandemic, challenge us reflect more deeply on hope. The author emphasizes that hope should be treated as “a faithful friend”, not merely as an abstract concept. With hope along the journey, we are empowered to survive in the midst of suffering, to face the waves of anxiety, and to transcend our frailty. By taking inspiration from Levinas’ philosophy and Metz’s theology, the author underlines that genuine hope encourages people to open themselves to God and the other(s).